Rediseño arquitectónico en base a criterio holístico de la unidad Luis Chiriboga Manrique en la parroquia Posorja - Hessmer Guaranda, Ronny Alexis (2024)
The architectural redesign of the Luis Chiriboga Manrique Educational Unit, based on a holistic approach, seeks to address various deficiencies in the current infrastructure of the educational center, located in the Posorja parish. Founded in Guayaquil in 1972 and moved to Posorja in 1984 due to structural damage due to the Niño phenomenon, the establishment currently faces problems of saturation in the classrooms and lack of adaptation to modern pedagogical needs. The problems include the lack of recreational areas, natural ventilation and accessibility, aspects that negatively impact the quality of learning and the well-being of students. The general objective of the project is to redesign the infrastructure to optimize space and adapt the environment to current needs, promoting a holistic approach that integrates technical, social and environmental aspects. This includes reconfiguring classrooms and common areas, incorporating sustainable technology and resources, and creating green and accessible spaces. The hypothesis suggests that these improvements will significantly increase the quality, comfort and functionality of the educational environment....